Alternative Parenthood: Interaction between the Concepts Parenting and Care - Stražinskaitė, Dalia; Zaleskienė, Irena (Pedagogika, 2017)
The changes of education paradigms and new tendencies of education allow to expand the content and expression of the educational function of child care having in mind all periods of child development and social reality situations. Foster care and parenting have been developed into individual theories over the past few decades, and the possibilities of potential combination of theories have not been realized. The research question raised by the authors: what kinds of interaction exist between concepts of “parenting” and “care”? The analyses of research works and empirical data discloses that an alternative parenthood is the creation of a particular communicative relationship between the child and the caregiver. Thus the relationship becomes a social phenomenon which embraces the concord between child-oriented educational activities and the creation of the caregiver’s identity. The educational function of foster care is manifested in the article: under specific education conditions; via the mutual dialogue between the child and his/her caregiver; at the stages of preparation, acquaintance, crisis and adaptation; through the caregiver’s skills and values. On the basis of the narrative analysis of caregivers’ interviews the model of the dialogic-procedural expression and conditions of the educational function of alternative care are devised. The axis of relationships underlined in the narratives of caregivers supplement the model of dialogical self-education described in the literature review and the classification of parenting skills. The axis of context is a constitutent part of external environment conditions, whereas the time axis gives prerequisites for dividing the process of foster care into stages. The model has a potential to reduce the number of unsuccessful cases of care, enables the specialists to identify the insufficiency of care conditions as well as to model the behavior of both participants of the care process. The process of care is expressed through dialogic self-education that enables both participants of interaction to express own needs and expectations, as well as change own thinking, behaviour and values. The participants of interaction participants exchange information through own behaviour, refusal to behave in the way asked, protest, silence, tears and other non-verbal expressions; however, language is especially significant in a dialogue both as a medium and as an educational means. In the model, skills are divided into child-centered, i.e. basic skills that manifest the functions of care as a mission, and adult-centred that are referred to as enhanced. The third distinguished aspect is the expression of caregivers’ values at different stages of care. At the end some conclusions are developed by the authors in the sense that care as an educational conception is used to define the educational function addressed at both biological and foster children: identification of the educational needs of a child, representation of the child, creation of positive environment and its application for specific needs of a child, as well as the influence of an adult on a child’s development up to adulthood. From the educational point of view, apart from the usual family activities, non-kinship foster parenting should be directed towards the establishment of affective relationships, overcoming developmental disorders and traumatic experiences, prevention of harmful habits and maintenance of relationships with biological families.